Invisible women: exposing data bias in a world designed for men - Perez, Caroline Criado (Gurugram Penguin Random House, 2019)
From government policy and medical research, to technology, workplaces, and the media. Invisible Women reveals how in a world built for and by men we are systematically ignoring half of the population, often with disastrous consequences. Caroline Criado Perez brings together for the first time an impressive range of case studies, stories and new research from across the world that illustrate the hidden ways in which women are forgotten, and the profound impact this has on us all.
Keywords: Big data Social aspects